Component-Based Design and Assembly of Heuristic Multiple Sequence Alignment Algorithms - Shi, Haihe; Zhang, Xuchu (Frontiers in Genetics, 2020)
In recent years, bioinformatics data has been increasing explosively, but the data itself is not information. The purpose of bioinformatics research is to obtain information with biological significance from a large number of data. Multiple sequence alignment is an important part of bioinformatics research, which is widely used in sequence homology detection, protein secondary and tertiary structure prediction, phylogenetic tree analysis and other fields. Existing research mainly focuses on the specific steps of the algorithm or is for specific problems, lack of high-level abstract domain algorithm framework. As a result, multiple sequence alignment algorithms are more complex, redundant and difficult to understand, and it is not easy for users to select the appropriate algorithm, as a result some computing errors may be caused. Through in-depth study and analysis of the Heuristic Multiple Sequence Alignment Algorithm (HMSAA) domain, a domain feature model and an interactive model of HMSAA components have been established according to the generative programming method. With the support of PAR platform, the algorithm component library of HMSAA is formalized, and a specific alignment algorithm is assembled, thus enables the improvement of the reliability of algorithm assembling. The work theoretically provides a valuable reference for the application of other biological sequence analysis algorithms.